1999
DOI: 10.1017/s1461145799001480
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in glutamatergic transmission via N-methyl-D-aspartate receptors in the hippocampus and striatum of rats behaviourally sensitized to methamphetamine

Abstract: We searched for changes in glutamatergic transmission via N-methyl-D-aspartate (NMDA) receptors in the hippocampus and striatum of rats behaviourally sensitized to methamphetamine (Meth). Prior to being given a challenge dose of Meth (2 mg/kg, s.c.), the rats were given Meth (4 mg/kg, s.c.) five times a week for 3 wk. Seven days after the challenge test, we examined glutamate (Glu) release from hippocampal and striatal slices evoked by 30 mm KCl, and NMDA-evoked dopamine (DA) release from striatal slices. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Yamamoto et al (1999) reported that glutamate release from the hippocampus was reduced in the MAP-sensitized rats as compared to control rats, while glutamate release from the striatum was higher in the MAP-sensitized rats. In our experiments, the ratio of amplitude of the presynaptic potential to the population EPSP indicates that MAP decreased glutamate release from the nerve terminal of the Shaeffer collateral, which is consistent with the biochemical observations of Yamamoto et al (1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Yamamoto et al (1999) reported that glutamate release from the hippocampus was reduced in the MAP-sensitized rats as compared to control rats, while glutamate release from the striatum was higher in the MAP-sensitized rats. In our experiments, the ratio of amplitude of the presynaptic potential to the population EPSP indicates that MAP decreased glutamate release from the nerve terminal of the Shaeffer collateral, which is consistent with the biochemical observations of Yamamoto et al (1999).…”
Section: Discussionmentioning
confidence: 97%
“…When damage is sufficient to cause cell death, it is by apoptosis (Deng et al 2002;Zhu et al 2006), likely secondary to generation of reactive oxygen species leading to caspase activation (Pubill et al 2005;Jiménez et al 2004;Yamamoto and Bankson 2005). Yamamoto et al (1999) reported that glutamate release from the hippocampus was reduced in the MAP-sensitized rats as compared to control rats, while glutamate release from the striatum was higher in the MAP-sensitized rats. In our experiments, the ratio of amplitude of the presynaptic potential to the population EPSP indicates that MAP decreased glutamate release from the nerve terminal of the Shaeffer collateral, which is consistent with the biochemical observations of Yamamoto et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of METH reduces the protein levels of NMDA receptors, including NMDA receptor 1 (NR1), in the hippocampus [22]. In addition, repeated administration of METH reduces immunoreactivities of NR1 and NMDA receptors comprising NMDA receptor 2A and 2B in the striatum [26]. Continuous stimulation of NMDA receptors induces desensitization of this type of receptor [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of METH (4 mg/kg) reduces NMDAR1, R2A, and R2B immunoreactivity in the striatum (Yamamoto et al 1999). Similarly, repeated AMPH administration induces longlasting down-regulation of NMDAR1 mRNA and protein levels in the NAC and prefrontal cortex (PFC) (Lu et al 1999).…”
Section: Discussionmentioning
confidence: 99%